Knowledge, attitude, practice of Pap smear and their associated factors among female staff of Universiti Sains Islam Malaysia, Nilai - Mohd Razi, Nuurain Amirah (2017)
Introduction: The poor practice of Pap smear especially in the developing countries has been a longstanding issue and causes high number of cervical cancer cases detected at late stages with poor prognosis. Global Cancer Statistics 2012 estimated a number of 527,600 cervical cancer cases and 265,700 deaths worldwide in 2012; majority were in the developing countries. Inadequate knowledge, awareness, and poor attitude towards Pap smear lead to the low uptake. In Malaysia, the National Health and Morbidity Survey IV reported that Pap smear uptake in Malaysia was only 12.8% in 2011.